2019
DOI: 10.1088/1742-6596/1399/3/033113
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain as a technology for the transition to a new digital economy

Abstract: The modern economy is gradually developing and shifting into a virtual economic system. The new digital economy serves as the new model of economic development and redesigns businesses based on utilizing information in b2b relationships. New information and network technologies are becoming significant factors of a globalizing economy and contribute to the rapid transition of the economy from a real economy bound by boundaries to a network one connected by the internet, ensuring digital economy development and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 7 publications
0
11
0
Order By: Relevance
“…Natalia [ 5 ] suggests that development of a digital economy contributes to business development and the use of innovative technologies. Mentsiev et al [ 6 ] contributed research indicating that a digital economy enables companies to expand their business scope by using the Internet, thus creating business value. Davies et al [ 7 ] found that a digital economy provides new opportunities for enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Natalia [ 5 ] suggests that development of a digital economy contributes to business development and the use of innovative technologies. Mentsiev et al [ 6 ] contributed research indicating that a digital economy enables companies to expand their business scope by using the Internet, thus creating business value. Davies et al [ 7 ] found that a digital economy provides new opportunities for enterprises.…”
Section: Literature Reviewmentioning
confidence: 99%
“…He pointed out that the digital economy could effectively improve the organizational form of enterprises and the cooperation efficiency of various departments (Balcerzak and Pietrzak, 2017). In addition, Mentsiev et al (2019) thought that the digital economy was a commercial and trade activity based on the Internet. E-commerce is a representative form of the digital economy.…”
Section: Digital Economymentioning
confidence: 99%
“…e virtual economy can achieve high-profit income through short-term investment when the market supervision is low, so it is accompanied by greater risks [18,19]. While the real economy is in operation, physical substances are cyclical in the formation and circulation stage, and only one cycle can be completed before a certain profit can be obtained.…”
Section: Two Kinds Of Economic Relationsmentioning
confidence: 99%